Phase I study of vorinostat with gefitinib in BIM deletion polymorphism/epidermal growth factor receptor mutation double‐positive lung cancer. Issue 2 (6th January 2020) - Takeuchi, Shinji; Hase, Tetsunari; Shimizu, Shinobu; Ando, Masahiko; Hata, Akito; Murakami, Haruyasu; Kawakami, Takahiro; Nagase, Katsuhiko; Yoshimura, Kenichi; Fujiwara, Tadami; Tanimoto, Azusa; Nishiyama, Akihiro; et al.
Abstract: Patients with epidermal growth factor receptor ( EGFR )‐mutated non‐small cell lung cancer (NSCLC) harboring BIM deletion polymorphism ( BIM deletion) have poor responses to EGFR TKI. Mechanistically, the BIM deletion induces preferential splicing of the non‐functional exon 3‐containing isoform over the functional exon 4‐containing isoform, impairing TKI‐induced, BIM‐dependent apoptosis. Histone deacetylase inhibitor, vorinostat, resensitizes BIM deletion‐containing NSCLC cells to EGFR‐TKI. In the present study, we determined the safety of vorinostat‐gefitinib combination and evaluated pharmacodynamic biomarkers of vorinostat activity. Patients with EGFR ‐mutated NSCLC with the BIM deletion, pretreated with EGFR‐TKI and chemotherapy, were recruited. Vorinostat (200, 300, 400 mg) was given daily on days 1‐7, and gefitinib 250 mg was given daily on days 1‐14. Vorinostat doses were escalated based on a conventional 3 + 3 design. Pharmacodynamic markers were measured using PBMC collected at baseline and 4 hours after vorinostat dose on day 2 in cycle 1. No dose‐limiting toxicities (DLT) were observed in 12 patients. We determined 400 mg vorinostat as the recommended phase II dose (RP2D). Median progression‐free survival was 5.2 months (95% CI: 1.4‐15.7). Disease control rate at 6 weeks was 83.3% (10/12). Vorinostat preferentially induced BIM mRNA‐containing exon 4 over mRNA‐containing exon 3, acetylated histone H3 protein, and proapoptotic BIMEL protein in 11/11, 10/11, and 5/11 patients, respectively. These data indicate that RP2D was 400 mg vorinostat combined with gefitinib in BIM deletion/ EGFR mutation double‐positive NSCLC. BIM mRNA exon 3/exon 4 ratio in PBMC may be a useful pharmacodynamic marker for treatment. Abstract : Vorinostat, in combination with gefitinib, induced acetylated histone H3 protein expression, as well as a decrease in the BIM mRNA exon 3/exon 4 ratio in PBMC from BIM deletion polymorphism/EGFR mutation double‐positive NSCLC patients. These results provide proof of concept that the combined therapy can mitigate the functional effects of BIM deletion polymorphism.